Giant African pouched rats (Cricetomys gambianus) that work on tilled soil accurately detect land mines. Issue 3 (11th May 2015) - Edwards, Timothy L.; Cox, Christophe; Weetjens, Bart; Tewelde, Tesfazghi; Poling, Alan
<x xml:space="preserve">Abstract</x> Pouched rats were employed as mine‐detection animals in a quality‐control application where they searched for mines in areas previously processed by a mechanical tiller. The rats located 58 mines and fragments in this 28, 050‐m2 area with a false indication rate of 0.4 responses per 100 m2. Humans with metal detectors found no mines that were not located by the rats. These findings indicate that pouched rats can accurately detect land mines in disturbed soil and suggest that they can play multiple roles in humanitarian demining.